Coherent photo-induced phonon emission in the charge-density-wave state of K0.3MoO3. (18th January 2019) - Rabia, K; Meng, F; Thomson, M D; Bykov, M; Merlin, R; van Smaalen, S; Roskos, H G
Abstract: We report on the observation of coherent terahertz (THz) emission from the quasi-one-dimensional charge-density wave (CDW) system, blue bronze (K0.3 MoO3 ), upon photo-excitation with ultrashort near-infrared optical pulses. The emission contains a broadband, low-frequency component due to the photo-Dember effect, which is present over the whole temperature range studied (30–300 K), as well as a narrow-band doublet centered at 1.5 THz, which is only observed in the CDW state and results from the generation of coherent transverse-optical phonons polarized perpendicular to the incommensurate CDW b -axis. As K0.3 MoO3 is centrosymmetric, the lowest-order generation mechanism which can account for the polarization dependence of the phonon emission involves either a static surface field or quadrupolar terms due to the optical field gradients at the surface. This phonon signature is also present in the ground-state conductivity, and decays in strength with increasing temperature to vanish above T ∼ 100 K, i.e. significantly below the CDW transition temperature. The temporal behavior of the phonon emission can be well described by a simple model with two coupled modes, which initially oscillate with opposite polarity.